FACTOR AFFECTING PROFESSIONAL LEARNING COMMUNITY OF TEACHER TOWARD THAILAND 4.0 IN SECONDARY SCHOOLS, LOEI PROVINCE - Pantuwapee, Nopparat (Journal of Social Science and Cultural, 2023)
This research aimed to study: 1) the professional learning community level, 2) the levels of factors relating to professional learning community, and 3) the factors affecting the professional learning community of teachers toward Thailand 4.0 in secondary schools in Loei Province. Methodology was the survey research analyzing data in quantitative methods. The sample group consisted of 319 teachers and directors from 31 secondary schools in Loei Province selected by simple random sampling. The research instrument was a questionnaire of the affecting factors the professional learning community. The statistics used in data analysis were mean, standard deviation, Pearson Correlation, and multiple regression analysis. The research results were as follows. Firstly, the study of opinion toward the performance relating in secondary schools was at high level, averagely 4.31. The top three factors ranked from highest scores were leaners’ learning, shared visions, and learning and professional development. Secondly, the level of opinion toward the professional learning community of teacher toward Thailand 4.0 was scored at high level, averagely 4.41. The top three factors ranked from highest to lowest scores were learning and applying knowledge together, creating value and shared visions, and having supportive conditions. Lastly, the factors found are related to the shared visions, professional learning and development, students’ learning, collaborative teamwork, caring community, leadership and supports, and supportive structure. As a result, the null hypothesis efficiency in prediction was 76.50 percent significantly rejected at 0.05 level. The study also found that the shared visions most highly affected the teachers’ professional learning community in secondary schools in Loei Province in Thailand 4.0 Era.